Assessing Technical, Cognitive, and Psychological Readiness of Prospective Auditors in the Era of Artificial Intelligence - Raff Iwata Anugrah Lamusa; Haryono Pasang Kamase; Tenripada (Owner : Riset dan Jurnal Akuntansi, 2026)
This study aims to analyze the influence of prospective auditors' readiness to face the era of Artificial Intelligence (AI), viewed from three dimensions: Technical Readiness, Cognitive Readiness, and Psychological Readiness. The research uses a quantitative approach with a survey method applied to 100 accounting students from various universities in Indonesia who have completed an auditing course. The data was analyzed using multiple linear regression with the help of SPSS version 16. The research findings indicate that all three dimensions of readiness Technical Readiness, Cognitive Readiness, and Psychological Readiness have a significant positive impact on AI acceptance. Together, these three variables are able to explain 45.3% of the variation in AI acceptance. This finding confirms that the readiness of prospective auditors is multidimensional, with the psychological aspect being the most dominant factor, followed by the cognitive and technical aspects. The implications of this research emphasize the importance of developing an accounting curriculum that not only focuses on technical skills but also builds AI literacy, critical thinking, and students' confidence in collaborating with AI technology.